Reflection of Ki Hajar Dewantara’s Character Education Philosophy on Independent Learning - Muhammad Hufron; Mahfud Junaedi (Edukasia Islamika : Jurnal Pendidikan Islam, 2021)
The character education carried by Ki Hajar Dewantara plays a role in preparing the nation's children to build and preserve the nation's identity that is characterized and cultured. The purpose of this study was to reflect on the thinking of Ki Hajar Dewantara's character education in the global era. The method used was qualitative with a philosophical approach. The research type was through an intellectual biographical. The analytical technique used was philosophical interpretative. Reflections on Ki Hajar Dewantara's philosophy of character education are relevant to be applied in the education curriculum in Indonesia, especially on the independent learning perspective in the digital literacy era. Ki Hajar Dewantara's character education emphasizes humanist values, based on reconstruction and nationalist spirit. Reflections on Ki Hajar Dewantara's character education have five basic aspects of character namely: smart, excellence, soft-skill, perfect, and global character education. Ki Hajar Dewantara's character education is relevant in the context of education in post-reformation Indonesia seen from the relevance of religiosity, ethical, social, cultural, and universality. Ki Hajar Dewantara's character education also helps to minimize various national multidimensional crises, namely: religious, moral, model, orientation, and social crisis solutions.